364 WHAT SHOULD WE INCLUDE IN A CULTURAL COMPETENCE CURRICULUM? A FORMATIVE EVALUATION. Issue 1 (1st January 2007) - Estrada, C. A.; Shewchuk, R. M.; Staton, L. J.; Bigby, J.; Houston, T. K.; Allison, J.
Abstract : Background and Objective: Designing a cultural competence curriculum is inherently complex. Many elements are needed, and multiple frameworks exist. We used a novel approach to identify and prioritize elements to include in a cultural competence curriculum to address disparities in cardiovascular disease. Methods: First, we used the nominal group technique (NGT) to generate and prioritize a list of ideas to include in the curriculum. NGT is a structured small group process that fosters creativity and equal participation of participants. We conducted four NGT sessions and elicited responses to "What sorts of things could be included in a curriculum that focuses on cultural competence training for physicians?" Participants of the NGT sessions were nine medical students, seven medicine residents, seven practicing physicians, and seven disparities researchers. To organize the ideas generated, we then asked 45 educators and researchers to group and rank the ideas based on their own perceptions of importance. Lastly, to produce homogeneous groupings of elements based on the ideas grouped and ranked, we used multidimensional scaling (MDS) and hierarchical cluster analysis. Results: The NGT sessions generated 61 ideas, 29 of which were selected by at least 2 participants. We observed five clusters of related issues within the multidimensional space: (1) patients' cultural background (provide information on cultures, * habits, customs, values); (2) impact on health care and health behavior (include factors influencing health services, folk remedies, diet); (3) differences in therapies and health disparities (provide pharmacologic therapies, reasons for cardiovascular disparities); (4) awareness of approaches to multicultural care (increased awareness of own biases, * "stereotype avoidance"); and (5) resources to manage cultural diversity (provide resources for patients and their families to comprehend instructions, * provide questions to permit taking a cultural history, * language translation guide and available services, community resources). The asterisks indicate the top-rated ideas by the NGT groups. The MDS showed good fit of the dimensions (stress = 0.074; R 2 = .97). Conclusions: Our cognitive mapping approach allowed us to use input obtained from various stakeholders and generate critical domains to guide the development of the new curriculum.